The economic burden of tuberculosis in Cyprus. A probabilistic cost of illness study. - Savvas Zannetos; Theodora Zachariadou; Tonia Adamidi; Andreas Georgiou (Epidemiology, Biostatistics and Public Health)
Background: Tuberculosis remains a major public health problem with considerable economic burden worldwide. The aim of this study was to estimate the economic burden of tuberculosis in Cyprus during 2009.